Adsorption/Desorption of Ammonium and Phosphorus on Four Substrates in Constructed Wetland - Zhang, Liping; Wen, Xiaodong; Zhang, Jian; Chen, Aolei; He, Xuwen (Asian Journal of Chemistry, 2015)
Gravel, clinoptilolite, limestone and lytag are widely used in constructed wetland in China. The results of adsorption kinetic study showed that the adsorption rate of ammonium on these four substrates was in the order: clinoptilolite > lytag > gravel > limestone, and the adsorption rate of phosphorus was: clinoptilolite > lytag > limestone > gravel. Meanwhile, pH value played an important role on removal efficiency of ammonium and phosphorus on four substrates. Clinoptilolite displayed the largest adsorption capacity of ammonium (average 0.289 mg/g) when pH was 6-8, and decreased obviously with increasing of pH until 9. When pH increased from 6 to 9, adsorption capacity of phosphorus on clinoptilolite significantly increased to 0.141 mg/g, while the value on lytag decreased from 0.138 to 0.092 mg/g. Both Freundilch and Langmuir model could well describe the adsorption behaviour of ammonium and phosphorus on the four substrates. Clinoptilolite and lytag demonstrated best removal efficiency of ammonium and phosphorus, respectively. Desorption experiments showed that gravel had the largest desorption ratio of both ammonium (27.6265 %) and phosphorus (41.7143 %). More importantly, the ammonium desorbed from lytag (35.2439 mg/L) could lead to ammonium secondary pollution, while all of the four substrates would result in phosphorus secondary pollution.